Viscosity dependence of intra- and intermolecular diels-alder reactions - Tiwari, Shraeddha; Kumar, Anil (Journal of Physical Chemistry A, 2012)
The kinetics of the bimolecular Die Is Alder reaction between anthracene-9-carbinol and N-ethyl maleimide have been studied in a series of pyridinium-based ionic liquids with the tetrafluoroborate ([BF4](-)) and the bis(trifluorosulfonimide) ([NTf2](-)) anions and the viscosity dependence of the rate constants have been compared with the results for the intramolecular Diels Alder reaction of (E)-1-phenyl-4-[2-(3-methyl-2-butenyloxy)benzylidene]-5-pyrazolone. The comparison leads to the surprising observation that the intermolecular reaction is less susceptible to viscosity variations of the ionic liquids as compared to the intramolecular reaction. The observed similarities and differences emphasize the complicated nature of solvent friction on the kinetics of cycloaddition reactions. The results are explained by considering the bimolecular and intramolecular processes as cases of translational and rotational diffusion, respectively. Plausible indicators of microviscosity consistent with the kinetic data for the Diels-Alder reactions are briefly discussed along with the constraints involved in designing a general microviscosity scale.